The role of arousal and motivation in emotional conflict resolution: Implications for spinal cord injury - Pecchinenda, Anna; Gonzalez Pizzio, Adriana Patrizia; Salera, Claudia; Pazzaglia, Mariella (Frontiers in Human Neuroscience, 2022)
Under many conditions, emotional information is processed with priority and it may lead to cognitive conflict when it competes with task-relevant information. Accordingly, being able to ignore emotional information relies on cognitive control. The present perspective offers an integrative account of the mechanism that may underlie emotional conflict resolution in tasks involving response activation. We point to the contribution of emotional arousal and primed approach or avoidance motivation in accounting for emotional conflict resolution. We discuss the role of arousal in individuals with impairments in visceral pathways to the brain due to spinal cord lesions, as it may offer important insights into the "typical" mechanisms of emotional conflict control. We argue that a better understanding of emotional conflict control could be critical for adaptive and flexible behavior and has potential implications for the selection of appropriate therapeutic interventions.